PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN VOUCER WIFI.ID PADA PT. TELKOM REGIONAL IV JAWA TENGAH & DAERAH ISTIMEWA YOGYAKARTA - SUSI INDRAWATI, 14.05.51.0124 (Students' Journal of Economic and Management, 2018)
This study aims to examine the effect of service quality, price perception and product quality on wifi.id vouchers purchasing decisions at PT. Telkom Regional IV & DIY, both partially and simultaneously. The type of data used in this research is primary data, namely data obtained directly from the original source. While the technique used for data collection uses a questionnaire by asking a number of written questions that are used to obtain information from respondents. The sample in this researcher is consumers who have made wifi.id vouchers purchasing decisions at PT. Telkom Regional IV Central Java & DIY Semarang City sales area of ​​100 people. The sampling technique used purposive sampling, namely sampling conducted in accordance with the research objectives that have been established, namely the criteria of wifi.id vouchers users at PT. Telkom Regional IV Central Java & DIY, in the sales area of ​​Semarang City. The test tool in this study uses multiple linear regression. The results of the analysis can be concluded that: Service quality has a positive effect on purchasing decisions. The better the quality of service, the purchasing decision will increase. Price perception has a positive effect on purchasing decisions. The better the price, the purchasing decision will increase. Product Quality has a positive effect on purchasing decisions. The better the quality of the product, the purchasing decision will increase. Service Quality, Price Perception and Product Quality have a positive positive effect on purchasing decisions. Keywords: Service Quality, Price Perception, Product Quality and Purchase Decision.